The Prospects of an Active Vaccine Against Asthma Targeting IL-5 - Bachmann, Martin F.; El-Turabi, Aadil; Fettelschoss-Gabriel, Antonia; Vogel, Monique (Frontiers in Microbiology, 2018)
Allergen-specific T helper type 2 (Th2) responses followed by eosinophilic inflammation of the lung are important causes of allergic asthma. Interleukin-5 (IL-5) is a master regulator of eosinophil-differentiation as well as activation. Blocking IL-5 using monoclonal antibodies (mAbs) against IL-5 is a powerful way to improve asthmatic symptoms in patients with an eosinophilic component of the disease. We have previously shown that vaccination against IL-5 can abrogate eosinophilic inflammation of the lung in allergic mice. More recently, we have demonstrated that eosinophil-mediated skin disease in horses with insect bite hypersensitivity can be strongly reduced by vaccination against IL-5. Here we would like to propose the development of a similar vaccine for the treatment of asthma in humans.